Can â€œGoyang Karawangâ€ Be a Brand of Karawang Tourism City? - Sumarni, Neni; Suherman, Enjang; Nurlenawati, Netti; Nasihin, Ihsan (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Goyang Karawang is one of the nicknames given to the city of Karawang, apart from